A study of dry eye disease at IIUM optometry clinic - Aljarousha, Mohammed A.M (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2016)
Dry eye (DE) is a multifactorial pathology which affects tear production and evaporation rate; and associated with diabetes mellitus (DM). The prevalence of DE is 7 to 34% worldwide. In Malaysia, however, the prevalence data and studies on the associations between DE symptoms and signs are limited. In addition, there is no data on tear functions assessments of diabetic patients. Therefore, the aims of this study were to determine the prevalence of dry eye disease (DED); identify the associations between DE symptoms and signs; and compare DE symptoms and signs between DM and non-DM; DM with and without DED in the Optometry Clinic International of the Islamic University Malaysia (IIUM) Kuantan. A retrospective analysis of DE and tear break up time test (TBUT) values were assessed in 643 files. Based on the diagnosis of dry eye from at least one reported symptom or TBUT< 5 seconds, the overall prevalence of DED was 48.8%, which was mainly due to the high number of diabetics and contact lens (CL) wear. Fifteen percent of the DE was based on symptoms while 26.7% by TBUT, indicating the importance of clinical sign in DE diagnosis. The prevalence of DED was higher in females than males. This might be due to the difference in the acinar size of lacrimal glands between the two genders, responsible for a higher tear volume in males than females. The prevalence of DED increased with age, 44.9% in < 50 years and 56.1% in ≥ 50 years (males); and 43.0% in ≤ 49 years and 68.4% in > 50 years (females) because of the alteration in tear function with increasing age. The risk factors associated with symptomatic dry eye disease were CL wear (adjusted OR=3.4; 95% CI=1.2-9.3) and a lower TBUT values (adjusted OR=2.3; 95% CI=1.0-5.1) in males. The study found that age ≥ 50 years (adjusted OR=1.9; 95% CI=1.0-3.6) and a lower tear meniscus height (adjusted OR=3.8; 95% CI=2.3-6.3) scores were the risk factors for dry eye symptoms in females. DM with DED had a significantly higher frequency of dry eye symptoms than DM without DED (p<0.001). TBUT was significantly different between DM and non-DM; DE (p<0.001) and between the DM (DE and the non-DE) (p<0.05). In addition, the number of patients with dry eye symptoms was significantly higher in diabetics than non-diabetics. Similarly, the number of diabetics with dry eye symptoms was significantly higher than diabetics without dry eye symptom (p<0.001). This study provided new information about the prevalence of dry eye disease and its risk factors in the East Coast of Peninsular Malaysia. Also, the results of this investigation may enhance the understanding of the relationship between DM and tear functions. In conclusion, the prevalence of DED among optometric outpatients is comparatively high with almost 50% of them diagnosed with dry eye disease. Symptoms and signs were poorly associated. Additionally, DED is more common among DM patients.